ROLE OF METABOLIC THERAPY IN TREATMENT OF MYOCARDIUM DYSTROPHY IN CHILDREN - A.L. Frolenko; M.V. Spaskova; N.N. Kagan; I.Yu. Skachkova (Вопросы современной педиатрии)
The objective of present research was studying of influence of co-enzyme Q10 (Kudesan) on cardiovascular system in children with myocardial dystrophy (MCD). Patients were divided on two comparable groups (n = 20 and n = 28) according to clinical symptoms of MCD, changes on electrocardiogram (ECG) and results of echocardiography. Patients received non-drug means (massage, physical training in treatment regimen, psycho- and reflexotherapy) and vasoactive, nootropic and sedative medications; patients from 2nd group were additionally treated with co-enzyme Q10 during 4 weeks. It was shown that inclusion of co-enzyme Q10 in complex treatment of MCD resulted in beneficial effect on self-feeling of child, favored to disappearance of repolarization disorders on ECG and increase of ejectional fraction. Thus, using of co-enzyme Q10 in complex treatment of children with MCD is reasonable. Key words: children, myocardial dystrophy, co-enzyme Q10, treatment.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(5):18-23)